Lithium tetraborate co-doping with transition and alkali metals - Zakharchuk, I.A.; Daibagya, D.S.; Osadchenko, A.V.; Danilkin, M.I.; Ambrozevich, S.A.; Selyukov, A.S. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
Luminescent properties of tissue-equivalent detectors have been studied. The detectors are made of lithium tetraborate and doped with magnesium, manganese, or tin. Analysis of the results obtained makes it possible to confirm the complexity of luminescence centers in lithium tetraborate without using structural analysis methods. For the first time, the effect of the method and order of introducing impurities on the storage properties of the studied materials was demonstrated and explained. The synthesis of the lithium tetraborate host occurred through the reaction of H3BO3 and Li2CO3. The binding agent was SiO2. Magnesium, manganese, or tin dopants were introduced during the synthesis of the host or later. The final stage of the synthesis was pressing of the powder into tablets and sintering in argon at 1158 K. The photoluminescence and pulsed cathodoluminescence signals were recorded by CCD-spectrometers. Portable pulsed electron accelerator was used for excitation of cathodoluminescence. Thermally stimulated luminescence was recorded by a special dosimetric reader with a heater and photo muliplier tube after exposure of the samples to an electron beam. Photoluminescence spectra, cathodoluminescence spectra, and glow curves were obtained for five samples of lithium tetraborate with various impurities, namely, magnesium, manganese, and tin. A comparison of the results was made to identify how the intensity signals depend on the amount of impurities and order of their introduction. It was found that the synthesis procedure and the order of introducing the dopants affect the luminescent properties of the materials. It has been suggested that the impurities take different positions in the lithium tetraborate structure. Predominant introduction of a particular impurity at a particular site leads to the following result. Doping with tin provides an increase in the number of luminescence centers of manganese and significantly sensitizes its luminescence, while doping with magnesium leads to the opposite result. The results indicate that it is possible to create advanced tissue-equivalent detectors with tailored luminescent. Depending on the dose of ionizing radiation, the use of material with different sensitivity and radiation resistance is required. Thus, the production of detectors based on lithium tetraborate and the described impurities in the future will give an opportunity to create a promising group of ionizing radiation detectors with various properties.